Analisis Balik Kestabilan Lereng Tambang Batubara Pit RTS-C Sisi Barat WUP Roto-Samurangau PT. Kideco Jaya Agung, Kecamatan Batu Sopang, Kabupaten Paser, Provinsi Kalimantan Timur - Bagas Maulana Hasan; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT Kideco Jaya Agung is a company engaged in coal mining business located in Paser Regency, East Kalimantan Province. The mining system is carried out using an open pit mining system. The RTS-C pit has a crack in the high wall area of the west side of section A at an elevation of 100 m /L, on the crest overall slope of section B there is a pond with a distance of 200 meters. Slope stability analysis is performed using the limit equilibrium method (bishop simplified method) and monte carlo probabilistic analysis. The results of the actual topographical analysis of Section A obtained values of SF 1.661 and PF 0.000%, the results of analysis in design of 2019 were SF 0.995 and PF 54.100%. The results of the actual topographical analysis of Section B obtained values of SF 1.351 and PF 0.000%, the results of analysis in design of 2019 were SF 0.926 and PF 92.100%. The values of material properties in the back analysis were c and ∅ are at 60% of the original condition (peak), mudstone material values of c = 79.2 kPa and ∅ = 16.11° for sandstone material values of c = 87.6 kPa and ∅ = 17.37 °.Keywords: Back analysis, slope stability, crack, bishop, monte carlo